Effects on maternal and pregnancy outcomes of first-trimester malaria infection among nulliparous women from Kenya, Zambia, and the Democratic Republic of the Congo. - Sequoia I Leuba; Daniel Westreich; Carl L Bose; Andrew F Olshan; Steve M Taylor; Antoinette Tshefu; Adrien Lokangaka; Waldemar A Carlo; Elwyn Chomba; Musaku Mwenechanya; Edward A Liechty; Sherri L Bucher; et al. (PLoS ONE)
Background Few studies have assessed the impact of first-trimester malaria infection during pregnancy. We estimated this impact on adverse maternal and pregnancy outcomes. Methods In a convenience sample of women from the ASPIRIN (Aspirin Supplementation for Pregnancy Indicated risk Reduction In Nulliparas) trial in Kenya, Zambia, and the Democratic Republic of the Congo, we tested for first-trimester Plasmodium falciparum infection using quantitative polymerase chain reaction. We estimated site-specific effects on pregnancy outcomes using parametric g-computation. Results Compared to uninfected women, we observed the adjusted site-specific prevalence differences (PDs) among women with first-trimester malaria of the following pregnancy outcomes: preterm birth among Congolese (aPD = 0.06 [99% CI: -0.04, 0.16]), Kenyan (0.03 [-0.04, 0.09]), and Zambian (0.00 [-0.10, 0.20]) women; low birth weight among Congolese (0.07 [-0.03, 0.16]), Kenyan (0.01 [-0.04, 0.06]) and Zambian (-0.04 [-0.13, 0.16]) women; spontaneous abortion among Congolese (0.00 [-0.05, 0.04]), Kenyan (0.00 [-0.04, 0.04]), and Zambian (0.02 [-0.07, 0.24]) women, and anemia later in pregnancy among Congolese (0.04 [-0.09, 0.16]), Kenyan (0.05 [-0.06, 0.17]), and Zambian (0.07 [-0.12, 0.36]) women. The pooled PD for anemia later in pregnancy (26-30 weeks) was 0.08 [99% CI: 0.00, 0.16]. Conclusions First-trimester malaria was associated with increased prevalence of anemia later in pregnancy. We identified areas for further investigation including effects of first-trimester malaria on preterm birth and low birth weight.